PROPOSTA DE BLUP GENÔMICO COM EFEITOS ADITIVOS E DE DOMINÂNCIA EM AMBIENTE R - SANTOS, Vinicius Silva dos; MARTINS FILHO, Sebastião; RESENDE, Marcos Deon Vilela de; SILVA, Fabyano Fonseca e (Brazilian Journal of Biometrics, 2017)
Recently, the dominance effects have been included in genomic selection of various species, being the GBLUP-D method the most widely used. This method consists in replacing, in the REML/BLUP procedure, the pedigree-based relationship matrices by marker-based relationship matrices. This method can be performed by means of GVCBLUP software or through R-package BGLR, which is based on Bayesian regression via Reproducing Kernel Hilbert Spaces – RKHS. In addition to these programs, we proposed the lmekin function implemented in the coxme package of R, which also allows the inclusion of additive and dominance genomic relationship matrices. In this context, we aimed to compare, via simulated data, the results from lmekin function with those from GVCBLUP software and BGLR. The results showed that the GBLUP and GBLUP-D methods fitted via REML in the GVCBLUP software and by means of the lmekin function are equivalent. The lmekin function is an efficient alternative for fitting genomic models with additive and dominance effects.